Orthostatic Hypotension in Hypertensive Adults: Harry Goldblatt Award for Early Career Investigators 2021. Issue 11 (4th August 2022) - Raber, Inbar; Belanger, Matthew J.; Farahmand, Rosemary; Aggarwal, Rahul; Chiu, Nicholas; Al Rifai, Mahmoud; Jacobsen, Alan P.; Lipsitz, Lewis A.; Juraschek, Stephen P.
Abstract : Orthostatic hypotension affects roughly 10% of individuals with hypertension and is associated with several adverse health outcomes, including dementia, cardiovascular disease, stroke, and death. Among adults with hypertension, orthostatic hypotension has also been shown to predict patterns of blood pressure dysregulation that may not be appreciated in the office setting, including nocturnal nondipping. Individuals with uncontrolled hypertension are at particular risk of orthostatic hypotension and may meet diagnostic criteria for the condition with a smaller relative reduction in blood pressure compared with normotensive individuals. Antihypertensive medications are commonly de-prescribed to address orthostatic hypotension; however, this approach may worsen supine or seated hypertension, which may be an important driver of adverse events in this population. There is significant variability between guidelines for the diagnosis of orthostatic hypotension with regards to timing and position of blood pressure measurements. Clinically relevant orthostatic hypotension may be missed when standing measurements are delayed or when taken after a seated rather than supine position. The treatment of orthostatic hypotension in patients with hypertension poses a significant management challenge for clinicians; however, recent evidence suggests that intensive blood pressure control may reduce the risk of orthostatic hypotension. A detailed characterization of blood pressure variability is essential to tailoring a treatment plan and can be accomplished using both in-office and out-of-office monitoring.